Investigation on Metal Adornments From Ancient Eastern Europe - Ghervase, Luminița; Dinu, Monica; Borș, Corina; Angheluță, Laurenţiu-Marian; Rădvan, Roxana; Cortea, Ioana-Maria (Frontiers in Materials, 2020)
The paper focuses on the investigation of certain bronze adornment objects from the First Iron Age (the so-called early Hallstatt period), dating to the 9th – 8th c. BC. These objects are part of a bronze and iron hoard (labelled Cx 116) discovered in the present Romanian territory, at Tărtăria – Podu Tărtăriei vest archaeological site, in Alba County. Along with a second hoard of bronze and iron objects, this represents a unique discovery for the present Romanian territory, namely for the inner Carpathian area and the Lower and Middle Danube Basin, where no such votive discovery had been made by archaeological excavations. The objects, approximately 450 bronze and iron objects – weapons, tools, adornments, and harnesses – were found in the two hoards, in the Southern ditch, which outlines the archaeological site. Digital radiography has been used to assess the physical state of the objects and to identify potential specific craftsmanship details. It showed a fairly good preservation status, with incipient corrosion processes located in the core of some of the objects and some specific traces of the crafting process and subsequent mechanical defects were highlighted. The relatively good state of preservation of the objects can result from the fact that they had been protected from the humid environment by the ceramic vessel they were placed in. XRF and LIBS were used to identify the materials and to stratigraphically evaluate the objects. XRF scanned the surface of the objects, revealing elements related to both the raw material – a copper alloy with tin and lead, together with trace elements related to the specific mining location of the ores, and to the depositional environment of the objects – such as iron. LIBS allowed a more in-depth stratigraphic analysis, which indicated a higher copper ratio - compared to iron - as the kinetic series advance, fact that sustains the idea that the major iron input was coming from the depositional environment. Both XRF and LIBS results were consistent with a high elemental variability, probably due to the nature of the original material and the influence of the burial soil conditions.